Sony Corporation - Fajer Alhashash; Tareq Alshammari; Abdulrahman Al-Mnaies (Journal of the Community Development in Asia (JCDA), 2019)
Sony Corporation is a multinational technology company that has been operating for more than 7 decades during which it has formed various partnerships. In today’s world, businesses are facing stiff competition; therefore, it is critical to invest in the right security technology. There are modern ways to go about it which include face detection technology which when coupled up with other existing practices will boost security. Facial recognition technology is not affordable for all business especially new startups and small business. By partnering with Sony, the facial recognition will be not only easy to integrate, fully automated, high levels of accuracy but also affordable for small businesses to acquire and use to boost security in their businesses.